RANCANG BANGUN ALAT PENGIRIS TOMAT MEKANIS (Design and Construction of Mechanical Tomato Slicer) - Rinal Arnando; Achwil Putra Munir; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2019)
ABSTRACT Slicing is reduction of the size of the foodstuffs into slices with a certain degree of thickness to be more easily processed into other products . The purpose of this research was to design, build and test of a  mechanical tomato  slicer. The parameters observed were effective capacity, percentage of damaged tomatoes, percentage of tomatoes not perfectly sliced and economic analysis.The results showed that the effective capacity was 39,27 kg/hour. The percentage of damaged tomatoes was 6%. Main cost in the mechanical  tomato slicer was Rp 118,10/kg  for the  first year; Rp 119,62/kg for the second year; Rp 121,24/kg for the third year; Rp 122,97/kg for the fourth year and Rp 124,82/kg for the fifth year. BEP of the mechanical tomato slicer was 616,06 kg for the  first year; 644,17 kg for the second year; 673,90 kg for the third year; 705,64 kg for the fourth year and 739,62 kg for the fifth year. NPV at 6,5% was Rp 275.775.273,7/year and internal Rate of Return of this equipment was 46,52 %. Key words: Tomato, Slicer, Mechanical ABSTRAK   Pengirisan dilakukan untuk mengecilkan ukuran bahan pangan menjadi irisan – irisan dengan tingkat ketebalan tertentu agar lebih mudah diolah menjadi produk lain. Penelitian ini bertujuan untuk mendesain, membuat dan menguji alat pengiris tomat mekanis. Parameter yang diamati yaitu kapasitas efektif alat, persenase tomat hancur,persentase  tomat teriris tidak sempurna dan analisis ekonomi.Hasil penelitian menunjukkan bahwa kapasitas efektif alat sebesar 39,27 kg/jam. Persentase bahan rusak sebesar 6 %. Biaya pokok alat pengiris tomat mekanis Rp 118,10/kg untuk tahun pertama; Rp 119,62/kg untuk tahun kedua; Rp 121,24/kg untuk tahun ketiga; Rp 122,97/kg untuk tahun keempat dan Rp 124,82/kg untuk tahun kelima. BEP pada alat pengiris tomat mekanis sebesar 616,06 kg pada tahun pertama; 644,17 kg pada tahun kedua; 673,90 kg pada tahun ketiga; 705,64 kg pada tahun keempat dan 739,62 kg pada tahun kelima. NPV alat pengiris tomat mekanis pada suku bunga 6,5% sebesar Rp 275.775.273,7/tahun dan nilai internal rate of return alat ini adalah sebesar 46,52 %.   Kata kunci : Tomat, Alat Pengiris, Mekanis